Fungal Septal Abscess Complicating Maxillary Sinus Fungus Balls in an Immunocompetent Host. Issue 3 (September 2015) - Patel, Rusha; Orlandi, Richard R.
Background: Fungal infections of the nasal cavity can be destructive entities that are typically seen in immunocompromised hosts. We present a case of a localized fungal abscess of the nasal septum in an immunocompetent host after endoscopic treatment of maxillary sinus fungus balls. Method: A 51-year-old woman with a history of asthma and recent treatment with oral steroids presented with bilateral maxillary sinus mycetomas. She underwent endoscopic sinus surgery. The postoperative course was complicated by an asthma flare, which required oral steroids. The patient returned with nasal obstruction, and results of a physical examination were consistent with a nasal septal abscess. Drainage was attempted, and cultures showed fungal elements. The abscess reaccumulated, and the patient was referred to our institution. Operative drainage was performed with placement of a catheter in the septal abscess cavity. Forty-eight hours of amphotericin irrigations were performed through this site. The patient was started on oral antifungal therapy. Results of an immune workup, including testing for human immunodeficiency virus and assessing immunoglobulin levels, were negative. Final fungal cultures grew Scedosporium apiospermum sensitive to voriconazole. The patient completed therapy without further recurrence. Follow-up at 6 months demonstrated no further recurrence of her fungal septal infection. Conclusion: Sinonasal fungal infections rarely occur in immunocompetent hosts. The septum may have been seeded during the endoscopic sinus surgery. The use of oral steroids may have been a risk factor for the development of an aggressive nasal septal fungal abscess in this patient. This is the first reported case of a nasal septal abscess in an otherwise immunocompetent host with S. apiospermum.